Controlling: integrative substance of financial management of enterprises - Buriak, Alina; Demianenko, Inna (My University, 2023)
Controlling as a functionally separate area of financial management, determined by the evolutionary progress of society. This is the newest concept of management, ideologically it is "management of management" according to the criterion of the rationality of using financial resources to achieve a common goal.

Контролінг як функціонально відокремлена сфера фінансового менеджменту, детермінована еволюційним прогресом суспільства. Це новітня концепція менеджменту, ідеологічно це «менеджмент управління» за критерієм раціональності використання фінансових ресурсів для досягнення спільної мети.
Keywords: controlling; financial management of enterprises; кафедра фінансів; контроль; управління фінансами підприємств